1988
DOI: 10.2466/pms.1988.67.2.656
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Numerosity as a Function of Item Size

Abstract: In a sample of 48 subjects, there was a significant inverse relation between item size and estimation of numerosity. This result was shown to be consistent with Gestalt theory. According to this approach, the components of good figures appear more numerous, and smaller items produce better figures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 9 publications
4
60
2
Order By: Relevance
“…As is presented in Table 1, the results of experiments in which experienced observers participated have shown little or no effect of element size and array area Burgess & Barlow, 1983). On the contrary, studies that have introduced naive or less experienced observers have shown the effects of element size and array area (Ginsburg & Nicholls, 1988;Shuman & Spelke, 2006;Sophian & Chu, 2008). Apart from human studies, it has been reported that extensive training was required, at least in the initial phase of an experiment, in studies that required animals to respond to numerosity under controls for perceptual variables (e.g., Nieder et al, 2002;Tomonaga, 2008).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As is presented in Table 1, the results of experiments in which experienced observers participated have shown little or no effect of element size and array area Burgess & Barlow, 1983). On the contrary, studies that have introduced naive or less experienced observers have shown the effects of element size and array area (Ginsburg & Nicholls, 1988;Shuman & Spelke, 2006;Sophian & Chu, 2008). Apart from human studies, it has been reported that extensive training was required, at least in the initial phase of an experiment, in studies that required animals to respond to numerosity under controls for perceptual variables (e.g., Nieder et al, 2002;Tomonaga, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, Burgess and Barlow (1983) demonstrated that display size and density had little ef-f f fect on precision in numerosity comparison by a 16-fold change of linear dimensions. As for the effect of element size, Ginsburg and Nicholls (1988), Shuman and Spelke (2006), and Sophian and Chu (2008) demonstrated an inverse relationship between item size and the estimation of numerosity, such as when larger items appeared less numerous than small items. By examining Weber fractions in the numerosity discrimination task, Ross (2003) demonstrated that when the size of elements in comparison was altered, the Weber fractions increased, suggesting that the difference in the size of elements elicited the deterioration of precision in numerosity comparison.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Human adults clearly have this ability when dealing with exact quantities labeled with Arabic numerals. Yet judgments of approximate numerosity in humans are consistently found to be highly influenced by sensory properties of the stimulus, such as regularity in a visual array, or frequency in an auditory sequence (Ginsburg, 1991;Ginsburg & Nicholls, 1988;Ginsburg & Pringle, 1988;Massaro, 1976). For example, the density and grouping patterns of large visual arrays affect the numerosity judgments of human adults (Durgin, 1995).…”
Section: Introductionmentioning
confidence: 99%